CME deflections due to magnetic forces from the Sun and Kepler-63. Issue Volume 15:Issue S354(2019) (June 2019) - Menezes, F.; Netto, Y.; Kay, C.; Opher, M.; Valio, A.
Abstract: The stellar magnetic field is the driver of activity in the star and can trigger energetic flares, CMEs and ionized wind. These phenomena, specially CMEs, may have an important impact on the magnetosphere and atmosphere of the orbiting planets. To predict whether a CME will impact a planet, the effects of the background on the CME's trajectory must be taken into account. We used the MHD code ForeCAT – a model for CME deflection due to magnetic forces – to perform numerical simulations of CMEs being launched from both the Sun and Kepler-63, which is a young, solar-like star with high activity. Comparing results from Kepler-63 and the Sun gives us a panorama of the distinct activity level and star-planet interactions of these systems due to the difference of stellar ages and star-planet distances.